Surveillance of Erythrovirus B19 (B19V) in patients with acute febrile illness suspected of arboviruses in Mato Grosso do Sul state, Brazil - Lichs, Gislene Garcia C.; Fernandez, Zoraida del Carmen; Nascimento, Valdinete Alves do; Alcantara, Daniel Maximo Corrêa; Lemos, Everton Ferreira; Carvalho, Cristiano M. Espínola; Demarchi, Luiz Henrique Ferraz; Gonçalves, Crhistinne Carvalho Maymone; Naveca, Felipe Gomes; Favacho, Alexsandra Rodrigues de Mendonça (Frontiers in Microbiology, 2024)
Introduction: Human Erythrovirus (parvovirus) B19 infection can produce symptoms similar to those produced by Dengue, Chikungunya, and Zika viruses, making clinical diagnosis difficult. The importance of erythrovirus B19 in human pathology has been increased and reported in numerous studies published globally.The B19V infection was investigated by real-time PCR in sera samples from patients with signs and symptoms related to classic arboviral symptoms. This study was conducted to provide information on the genetic diversity of Human Erythrovirus B19 (B19V) circulating in the state of Mato Grosso do Sul, Midwest region of Brazil, from 2017 to 2022. A total of 773 sera samples of patients with negative diagnostic results for Dengue, Chikungunya, and Zika, during the study period were analyzed.Results: Erythrovirus DNA was found in 10.6% (82/773) of patients, among them 10 were pregnant women. Four samples were completely sequenced, and the other five partially, to genotype by phylogenetic reconstruction. All samples belong to worldwide dispersed genotype 1, subgenotype 1a.The findings of the study demonstrate the importance of including B19V in differential laboratory diagnosis for epidemiological purposes and appropriate patient management. The diagnosis for B19V should be performed, particularly among pregnant women, immunocompromised patients, and individuals with hemolytic diseases, given that the infection is more severe in these cases.